Pengaruh Corporate Governance, Kinerja Keuangan, dan Ukuran Perusahaanterhadap Pengungkapan Sustanbility Reporting: Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021 - Ira Suryani; Yanti; Awaliawati Rachpriliani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to analize corporate governance, financial peformance and company size in sustainability reports. This research uses quantitathive methods. Data collection uses annual reports and sustainability reports of manufacturing companies listed on the Bursa Efek Indonesia (BEI) and aslo sustainability report for 2019-2021. Purposive sampling technique was used for sampling. The data was analyzed by testing. Inner model, outer model and hypothesis testing using SmartPLS version 3.0 software. The study results show that corporate gevornance and financial performance have a significant effect on sustainability report disclosure, while company size does not affect sustainability report disclosure.